Formulasi sabun mandi cair dari daging putih buah semangka (Citrullus lanatus) - Nurul Arfiyanti Yusuf; Nurul Sari Pandewa; Vilia Payangan; Diaz Permata (Sasambo Journal of Pharmacy, 2021)
White flesh watermelon (Citrullus lanatus) is known to contain alkaloids, flavonoids, tannins and polyphenols. Research conducted by Rimando proves that watermelon rind contains the amino acid citrulline reaching 60% which is important in increasing levels of nitric oxide which is a regulator of blood flow, muscle energy metabolism, and mitochondrial respiration during exercise. This study aims to formulate bath soap from watermelon waste that meets the requirements with variations in the concentration of watermelon flesh extract (3%; 6%; 9%). Watermelon flesh extract was extracted by maceration process using 70% ethanol. Evaluations were carried out in the form of organoleptic, pH, free of alkali, high foam and density. The results showed that the three formulas were formulas that met the requirements according to SNI standards based on pH test, free alkali, foam height, and density.